2020
DOI: 10.1002/pro.3832
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the catalytic C‐lobe of the HECT‐type ubiquitin ligase E6AP

Abstract: The HECT-type ubiquitin ligase E6AP (UBE3A) is critically involved in several neurodevelopmental disorders and human papilloma virus-induced cervical tumorigenesis; the structural mechanisms underlying the activity of this crucial ligase, however, are incompletely understood. Here, we report a crystal structure of the C-terminal lobe ("C-lobe") of the catalytic domain of E6AP that reveals two molecules in a domain-swapped, dimeric arrangement. Interestingly, the molecular hinge that enables this structural reo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 28 publications
0
13
0
2
Order By: Relevance
“…TRIP12 protein domains are conserved during evolution and are subject to post-translational modifications that likely modulate its structure and activity. Several studies reported HECT, ARM repeats, and WWE crystal structure of other proteins [ 16 , 17 , 18 ]. However, TRIP12 has yet to be recovered in crystal form to establish its complete 3D structure.…”
Section: Trip12 Protein Structure and Domainsmentioning
confidence: 99%
“…TRIP12 protein domains are conserved during evolution and are subject to post-translational modifications that likely modulate its structure and activity. Several studies reported HECT, ARM repeats, and WWE crystal structure of other proteins [ 16 , 17 , 18 ]. However, TRIP12 has yet to be recovered in crystal form to establish its complete 3D structure.…”
Section: Trip12 Protein Structure and Domainsmentioning
confidence: 99%
“…This is corroborated by the NOESY data that shows the I827 amino acid side chain methyl groups make numerous NOE contacts to several different surrounding hydrophobic side chains including T774, Y776, I787, F790, W791, L824, and M825 ( Fig 4 ). The same rationale would apply to the newly published structure of the domain-swapped E6AP dimer (PDB 6TGK), as I827 is still found embedded in the monomeric hydrophobic core and is not involved in the dimerization interface [ 63 ]. This structural disruption likely induces an allosteric change that reduces the catalytic activity and leads to its subsequent aggregation.…”
Section: Resultsmentioning
confidence: 99%
“…The crystal structure of UBE3A catalytic HECT domain was solved both in the apo form (PDB accession code: 1D5F; resolution: 2.8 Å) and in complex with the UBCH7 conjugating enzyme fragment comprising residues 495 to 852 (PDB accession code: 1C4Z; resolution: 2.6 Å) (Figure 3A). The HECT domain is a 40-kD carboxy-terminal catalytic domain that performs four main functions: (i) specific E2 binding; (ii) formation of a thioester intermediate with a Ub molecule transferred from the E2 ligase; (iii) Ub transfer to the ε-amino groups of lysine side chains on the protein substrate and catalysis of isopeptide bond formation; (iv) transfer of additional Ub molecules to the growing end of the multi-Ub chain [40,94].…”
Section: Ube3a Structure and Its Role In Mhtt Ubiquitinationmentioning
confidence: 99%